Exploring the causal links between cigarette smoking, alcohol consumption, and aneurysmal subarachnoid hemorrhage: a two-sample Mendelian randomization analysis - Lin, Heng; Yin, Yanqing; Li, Jie; Liu, Siwei; Long, Xiaoao; Liao, Zhuangbin (Frontiers in Nutrition, 2024)
Background: Aneurysmal subarachnoid hemorrhage (aSAH) represents a critical health concern characterized by elevated mortality and morbidity rates. While both genetic predisposition and lifestyle choices influence aSAH susceptibility, untangling the causative associations between cigarette smoking, alcohol consum ption, and aSAH risk remains imperative. Mendelian randomization (MR) offers a robust methodological framework for dissecting these relationships, leveragin g genetic variants as instrumental variables.Objective: This study employs a Two-Sample Mendelian Randomization (TSM R) approach to elucidate the causal connections between genetically determined cigarette smoking, alcohol consumption, and aSAH risk. Methods: Genetic instruments associated with cigarette smoking and alcohol co nsumption were sourced from the GWAS and Sequencing Consortium of Alcoh ol and Nicotine use (GSCAN). Leveraging a genome-wide association study (G WAS) dataset encompassing aSAH cases and controls of European ancestry, TS MR, utilizing the Inverse Variance Weighting (IVW) method, was employed to estimate causal effects. Rigorous criteria were applied for instrumental variable selection to ensure robust Mendelian randomization analysis.Results: Genetically determined cigarette smoking demonstrated a significant ca usal association with aSAH risk, with a 1-standard deviation increase in cigaret te use genetically linked to a 96% relative risk elevation (OR-IVW = 1.96, 9 5% CI = 1.28-3.01, p = 0.0021). However, genetically determined alcohol cons umption did not exhibit a statistically significant association with aSAH risk (O R-IVW = 1.22, 95% CI = 0.61-2.45, p = 0.578).: Mendelian randomization analysis unveils a causal nexus between cigarette smoking and heightened aSAH risk, advocating for targeted smoking c essation interventions within genetically predisposed cohorts. Conclusions regard ing the relationship between alcohol consumption and aSAH are hindered by in sufficient statistical power. Prudent interpretation of findings underscores the li mitations of Mendelian randomization in elucidating intricate genetic epidemiolo gical relationships. Continuous investigation with larger cohort sizes and advanc ed methodological approaches is indispensable for comprehensive comprehension of aSAH's genetic underpinnings.